PERANCANGAN SISTEM INFORMASI CUTI MENGGUNAKAN METODE RUP PADA PT GLOBAL NIKEL MULTIGUNA - Addin Nur Zaman; Haisyam Maulana; Rian Dwicahya Supriatman (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
PT. Global Nikel Multiguna still applies a manual system in leave management. This process causes delays, risks of recording errors, data manipulation, and document accumulation. This study was conducted to design a more effective and efficient web-based leave information system using the Rational Unified Process (RUP) method with four main phases: inception, elaboration, construction, and transition. Research data were collected through observation and interviews with the company, then analyzed to formulate system requirements. System modeling was carried out using the Unified Modeling Language (UML) method, followed by interface design in the form of wireframes, and an initial implementation using the Laravel framework. To ensure the functionality works as intended, functional testing was conducted using the black box method. The results show that the designed system can perform basic functions, namely leave submission, leave approval, employee data management, and report generation according to the company’s needs. However, this study is still limited to the design and initial testing stages, thus it does not yet include deployment and direct user evaluation, and further development is required so that the system can be fully implemented in the company.